Faktor Risiko Kejadian De Quervain Syndrome pada Pemain Game Online Mobile Legends Bang Bang - Lia Dwi Prafitri; Indah Aulia Afkan; Sigit Prasojo (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
The internet is not only used to find information but also as a means of entertainment such as playing online games. One of teenagers’ most popular online games is Mobile Legends Bang Bang. Playing mobile legends bang bang games excessively can cause a risk of repeated injuries that lead to de quervain syndrome. This study aims to: determine the risk factors for the incidence of de quervain syndrome in E-sport UKM Saint NU Institute of Technology Pekalongan. This study used quantitative methods with an analytical observational research design with a cross-sectional approach. The population of members of the E-sport UKM Institut Teknologi and Saint NU Pekalongan is 60. A sample of 53 corresponds to the of inclusion and exclusion criteria of the total population. Data analysis using fisher test. The results of this study, where the age with the category of late adolescence as much as 42 (79%). The duration of playing online games is 44 (83%) in the high player category. There were 38 respondents (72%) positive for de quervain syndrome as evidenced by the finkelstein test. Based on data analysis using the Fisher test, a p value of 0.040 was obtained for the relationship of age with de quervain syndrome and a p value of 0.037, so there is a relationship between age and de quervain syndrome and there is a relationship between the duration of playing online games with de quervain syndrome. The results of this study can be a reference and understanding of ergonomic and musculoskeletal physiotherapy related to cases of de quervain syndrome caused by age and duration of playing online games.